FROM BOYCOTT TO BUYCOTT: HOW SOCIOPOLITICAL CRISES SHAPE BRAND TRUST, PREFERENCE, AND INTENTION TO PURCHASE BISCUIT PRODUCTS IN INDONESIA - Salsabila Dona Sunandi; Dr. Nita Garnida (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Consumer boycotts have become a form of political consumerism that shapes brand evaluation, yet little research addresses habitual, low-involvement fast-moving consumer goods (FMCG) categories. This study examines how sociopolitical boycott sentiment, triggered by the 2023 Israel-Palestine conflict, influences Brand Trust, Brand Preference, and Purchase Intention toward multinational and local biscuit brands (Oreo and Roma) in Indonesia. A sequential explanatory mixed-method design combined Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data from 300 valid Indonesian biscuit consumers with thematic analysis of ten in-depth interviews. Results show that boycott sentiment significantly but weakly reduces Brand Trust, Brand Preference, and Purchase Intention, while Brand Trust strongly drives Brand Preference and Brand Preference remains the strongest determinant of Purchase Intention. Mediation analysis confirms that Brand Trust and Brand Preference partially mediate the boycott-purchase intention relationship. Qualitative findings reveal that consumers separate moral concern from product evaluation, relying on accumulated trust, taste, familiarity, and household habit, while expecting transparent, culturally sensitive, and action-based responses from multinational brands. The study extends political consumerism and brand equity literature by showing that boycott effects in habitual FMCG categories are evaluative rather than binary, and offers managerial guidance for sustaining brand resilience during sociopolitical crises.